Elucidating the oxidation mechanism of scopolamine derivatives via electrochemistry, UV–Vis, and NMR - Aguirre-Quintana, M; Aguirre-Quintana, M; Pizarro-Reyes, J; Pizarro-Reyes, J (Elsevier B.V., 2026)
Selective field detection of scopolamine derivatives is challenged by ambiguous mechanistic interpretations of the redox pathway. Here, the oxidation behavior of scopolamine hydrobromide (SHBr) and scopolamine N-butyl bromide (SBBr) at pH 2 on unmodified glassy carbon and platinum electrodes was studied using voltammetry, in situ UV–Vis spectroelectrochemistry, and multinuclear NMR. All faradaic signals arise from Br−/Br2oxidation, with SHBr exhibiting a characteristic secondary peak possibly attributable to –OH oxidation at 1.46 V vs. SCE. Identical λmax(∼385 nm) in UV–Vis spectroscopy and unchanged NMR resonances confirm the absence of organic-site oxidation, revealing only acid-catalyzed hydrolysis. We propose a unified proton-electron mechanism in which protonated ammonium moieties remain electrochemically inert under acidic conditions, enabling selective bromide detection. As a mechanistic proof-of-concept, these findings demonstrate that the oxidation mechanism of brominated scopolamine derivatives can be elucidated using simple, unmodified glassy carbon electrodes. This mechanistic baseline provides a foundation for a future rational design of electrode interfaces tailored to bromide-based scopolamine derivative detection. © 2025 Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.